(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of the study is to describe and present the process of accessing information resources in a secure military computer network as generalized net model. A simulation of the model was carried out using specialized software for working with generalized nets - GN IDE, and the most important results are visualized in the report.